2019
DOI: 10.1038/s41467-018-08162-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-deficient G-protein-biased μ-opioid receptors improve analgesia and diminish tolerance but worsen opioid side effects

Abstract: Opioid analgesics are powerful pain relievers; however, over time, pain control diminishes as analgesic tolerance develops. The molecular mechanisms initiating tolerance have remained unresolved to date. We have previously shown that desensitization of the μ-opioid receptor and interaction with β-arrestins is controlled by carboxyl-terminal phosphorylation. Here we created knockin mice with a series of serine- and threonine-to-alanine mutations that render the receptor increasingly unable to recruit β-arrestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
257
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(289 citation statements)
references
References 44 publications
14
257
2
Order By: Relevance
“…It has been proposed that hMOR endocytosis is closely associated with the development of drug tolerance in the opiate user and in mouse models . Our data reveal that A01 and A02 demonstrated low levels (~15%) of hMOR internalization with similar drug potency for Gα i coupling.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It has been proposed that hMOR endocytosis is closely associated with the development of drug tolerance in the opiate user and in mouse models . Our data reveal that A01 and A02 demonstrated low levels (~15%) of hMOR internalization with similar drug potency for Gα i coupling.…”
Section: Discussionmentioning
confidence: 58%
“…Ser 375 , that are phosphorylated by GRKs reveal that respiratory depression and constipation are significantly exacerbated when MOR receptors fail to internalize after agonist binding 14 while analgesic tolerance is reduced. Thus, perhaps the pursuit of new opioids that better mimic the endogenous system might result in novel more "balanced" agents with improved clinical utility over morphine-like derivatives.…”
Section: Mutations Of Carboxyl Tail Serine and Threonine Residues Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the hyper locomotor activity induced by heroin in mice may stimulate respiration and obscure any decrease in tidal volume. This would not occur with the high dose of fentanyl we tested as it reduced locomotor activity but may occur at lower doses which do enhance locomotor activity (Kliewer et al, ; Varshneya et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that fentanyl does not exhibit arrestin bias in arrestin translocation and GTPγS binding assays (McPherson et al, ; Rivero et al, ). Furthermore, in transgenic mice in which all the phosphorylation sites on the C tail of the μ‐opioid receptor had been mutated to alanine and which are therefore not phosphorylated by G protein receptor kinases (GRKs) and do not recruit and bind arrestins, fentanyl still depressed respiration (Kliewer et al, ). This observation brings into question the concept that opioid depression of respiration is a function of arrestin signalling (Montandon & Slutsky, ).…”
Section: Discussionmentioning
confidence: 99%